ПРОБЛЕМИ ФОРМУВАННЯ ПРАВОВОЇ СВІДОМОСТІ ШКІЛЬНОЇ МОЛОДІ (Педагогіка вищої та середньої школи, 2008)
Becoming of Ukraine as the rights state are depended on the level of citizens' lawfull condition, by the development of the democratic institutes, which define social-low activity ofpeople. That's why to form an effective system of the lawful formation of citizens, first of all the young people, who shall define the state of our country in the future, is one of the present interest question in our days.